Local Government Innovation in Implementing Mandatory Authorities in The Health Office Central Lombok District - Syaefullah Syaefullah; Arif Darmawan; V Rudi (Green Publisher Indonesia, 2022)
The research objectives are; 1. To see the innovation process in the health office for health sector affairs 2. To analyze the models/types of innovation that exist in the health office. 3. To map the obstacles/barriers in the innovation process at the agency. 4. To analyze the efforts made in overcoming these obstacles. This study uses a qualitative approach, data obtained through interviews, observation, and documentation with spiral data analysis. Discussion, the process of innovation in the health department is by disseminating findings, externalizing findings, combining findings and internalizing findings. The results of the innovation process and innovation model at the health office in the work unit made a breakthrough program that was applied with the following model: 1. Bajang Tastura (Ambulance Network Brigade), Rapid Ambulance Assistance for villagers, 2. P3KM (Infectious Disease P2 Agent), Recording of infectious diseases in the community, 3. PTM Posyandu, Monitoring of Non-Communicable Diseases, 4. P3S (Stunting Acceleration Program), 5. E-PPGBM (Mobile Toddler Nutrition Growth Monitoring), 6. Integrated Referral for MCH-ELDERLY and Adolescent-UKS Monitoring Elderly health in adolescent health, 7. E-Puskesmas, Online -based basic health services , 8. Quick Quin Blood, UTD implementer.